Pelatihan Financial Technology untuk Bertransaksi dan Berinvestasi - Faizal Rizky Yuttama; Alfizi Alfizi; Budi Widadi (LPPM Universitas Harapan Bangsa Purwokerto, 2022)
The emergence of changes in the technology industry makes developments in several related industries. One of them is in finance. The rapid development of financial technology creates a new era in society. Ease of transaction and investment by prioritizing digital technology. Collaboration between finance and technology that makes transactions more time efficient. People’s ignorance of current technological developments certainly leaves a bad impression on how the technology is implemented. All forms of adaption are neede, especially if there are regulations needed. Thus empowerment is one way in an effort to be able to help increasse understanding of financial literacy in supporting a digital technology-minded society. Increasing the capacity of human resources will make sustainable development that can increase the level of business development better. In this case, we strive to do community service by providing knowledge and training for the millenial generation.